Design of Active Sites on Nickel in the Anode of Intermediate‐Temperature Solid Oxide Fuel Cells using Trace Amount of Platinum Oxides. Issue 8 (14th June 2018) - Rednyk, Andrii; Mori, Toshiyuki; Yamamoto, Shunya; Suzuki, Akira; Yamamoto, Yuta; Tanji, Takayoshi; Isaka, Noriko; Kúš, Peter; Ito, Shigeharu; Ye, Fei
Abstract: In recent years, the lowering of the operation temperature of solid oxide fuel cells (SOFCs) has attracted much attention owing to the trade‐off between the best performance and the life span of SOFCs. For this challenge, new active sites on the Ni surfaces in a Nickel–Yttria‐Stabilized Zirconia (Ni‐YSZ) cermet anode of SOFCs have been created by deposition of trace amounts of platinum oxide (PtO x ) followed by an activation step of the anode at 1073 K in a hydrogen flow. The internal resistance (IR) free value (185 mA cm −2 at 0.8 V) observed for the single cell with an anode sputtered with a trace amount of PtO x (Pt content in anode: from 9 to 91 ppm) at 973 K is conspicuously higher than that of a similar single cell with a nonsputtered cermet anode (85 mA cm −2 ) at 0.8 V and 1073 K. Transmission electron microscopy microanalysis shows that the defect structure is formed on a partially oxidized Ni surface by active Pt species. Also, surface atomistic simulation on NiO (111) predicts the formation of Frenkel defect clusters with Pt cations, which partially cover the Ni surface. The formation of Frenkel defect clusters on the partially oxidized Ni surface (i.e., creation of new active sites for formation of water molecules) promotes the anode reaction, resulting in improvements in the anode performance of SOFC single cells at 973 K. Design of the aforementioned new active sites on Ni through sputtering of trace amounts of PtO x provides a great opportunity for "radical innovation" in the design of intermediate‐temperature SOFCs. Abstract : Radical innovation : Frenkel‐type defect clusters as new active sites on Ni in the anode of solid oxide fuel cells promote the fuel cell reaction drastically. The new active sites are designed by using trace amount of species such as Pt cations and remnant oxygen on the Ni surface, leading to an intermediate‐temperature solid oxide fuel cell showing extremely high anode performance at a high‐power generation efficiency level (see figure).